Studi Terhadap Tingkat Pelembagaan Politik PDI P Jawa Tengah - PrayitnoÂ , Budi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2012)
Political parties are important instrument for democracy. Party plays a very strategic link between the processes of government by citizens. In fact, a political party actually determines democracy. Finally, the party is a very important institution for the enhanced degree of institutionalization in democracy. Indonesian Democracy Party of Struggle (PDIP) is one political party which has a long pursuit in the history of parties in Indonesia. But many voters said that the Indonesian Democratic Party of Stuggle yet institutionalized. This assessment set out from the large influence of the Chairman of the PDIP Megawati Sukarnoputri. Relying on this condition, this study aims to determine the degree of political institutionalization Indonesian Democracy Party of Struggle. In this study, the author uses PDIP of Central Java which diverges in the region as an object of research. In assessing the degree of political institutionalization PDIP of Central Java, the author uses five parameters, namely (1) Systemless (2) Value infrsion (3) Decisional autonomy (4) Reification (5) Age of the organization. This study using qualitative methods through interviews with political elites in PDIP of Central lava. This interview was conducted against the elites who are considered competent to answer the question in this study. Meanwhile, to measure the degree of public knowledge of PDIP, the author also conducted a sample survey with nonprobability sampling methods. This survey conducted on IOU respondents spread over seven districts / cities in Central Java that includes, Semarang, District Kendal, Demak, Semarang District, Magelang District, Kudus, Purwodadi. Respondents used in this research are people who are considered eligible to participate in the survey, those who already have the right to vote in the election with a variety of professional backgrounds. The results showed that the political institutionalization of Central Java Indonesian Democratic Party of Struggle still in a low degree of institutionalization. This conclusion is drawn from the assessment of research results in each parameter used. This condition occurs due to the dominance of main political elite of Indonesian Democratic Party of Struggle which always intervention in determining all political decisions in the area, DPD PDIP Java as the representative of the local party acted only as an object of the patient from the decision issued by the central elite of PDIP.